Introduction to Environmental Awareness: Understanding the Importance of Environmental Preservation (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Environment refers tothe sum total of condition and influence that affects the life and developmentof organism. The qualitative development and quantitative progress of mankinddepends on the quality of environment. Therefore, there are no two views aboutthe fact that, it is the primary responsibility of man not only to preserve theenvironment but also to improve it qualitatively.